Human Aspects of Agile Transition in Traditional Organizations - Pinton,Mariângela (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2020)
Abstract: The agile transition is crucial for traditional organizations to remain competitive in the current market, which is characterized by a fast-pace and a constant need for innovation. In order to implement this transition, organizations must adjust their mindset to the new agile values. Despite its evident benefits, the transition to agile model is complex and time-consuming, posing many challenges to organizations. Since the agile philosophy is people-centered, rather than process-centered, most challenges are related to the human aspects of this transition and they demand a large transformation in all areas of the organization. This article provides a Systematic Literature Review (SLR) of the human aspects of agile transition and summarizes the existing literature into three categories: People, Management and Organization. Its main objective is to assist organizations undergoing agile transition in reducing risks related to this process, by acquiring knowledge on the challenges involved and implementing the proposed recommendations.